CAN DIFFERENT LEARNING STYLES IMPACT EFL LEARNERS' TOEFL ACHIEVEMENT? - Palupi, Asti Diah; Suwartono, Tono; Sukawati, Dewi (Premise: Journal of English Education and Applied Linguistics, 2024)
Educators need insights into how various learning styles can influence learners' performance in assessments. Exploring the impact of different learning styles on EFL learners' TOEFL reading achievement is a multidimensional endeavor with implications for educators, learners, and the broader society. This study aims to investigate the extent to which vocational diploma EFL learners acquired English based on their preferred learning styles. The ex-post facto design was used for this study. As many as 37 participants were selected purposely from all majoring fourth semester students at an EFL vocational diploma college. A questionnaire was used to divide the participants into three groups depending on their preferred learning styles: visual, auditory, and kinesthetic. A TOEFL reading test was employed to measure the participants’ English proficiency. The average scores for each learning style group were calculated and revealed that visual learners had an average TOEFL reading score of M=43.22, kinesthetic learners had an average TOEFL reading score of M=38.70, and auditory learners had an M=35.00. To statistically compare these averages, one-way analysis of variance (ANOVA) was used. The ANOVA results showed a non-significant finding with df=2, F=1.102 and P=0.344. The findings revealed that the TOEFL reading comprehension scores of students with different learning styles did not differ significantly. This study contributes to the ongoing discourse surrounding individualized learning experiences and standardized language assessments. As the field of language education continues to evolve, further research will be pivotal in refining pedagogical practices to better meet the diverse needs of learners striving to excel in their language proficiency endeavors.